Internal Control Sebagai Moderasi Dalam Hubungan Financial Distress Dengan Accrual Earnings Management - Jessica, Elsa Imelda (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to obtain empirical evidence on the influence of financial distress on earnings management as well as the moderation effect of internal control in the relationship of financial distress with earnings management in manufacturing firms listed on the Indonesia Stock Exchange during the period 2017-2019. The research design used to test the influence of independent variables on dependent variables and the influence of moderation variables in the relationship is a descriptive research with purposive sampling method, and obtained as many as 105 samples of companies. Then, the hypothesis testing is done by panel data regression model and moderation regression model. This research was conducted using EViews (Econometrical Views) 11 application. This study obtained the results that financial distress has a significant positive influence on accrual earnings management, and there is a moderation effect of internal control that weakens the relationship of financial distress with accrual earnings management. The implication of this study is firms with greater financial distress have a higher level of accrual earnings management and the need to increase firms’ internal control to restrict firms’ accrual earnings management.